REPRESENTASI REALITAS SOSIAL MELALUI ESTETIKA SASTRA DALAM NOVEL FILOSOFI KOPI KARYA DEE LESTARI - Rauf, Harnida; Andi Karman; Aslan Abidin (STKIP Subang, 2026)
This study aims to describe the representation of social reality through literary aesthetics in the novel Filosofi Kopi by Dee Lestari. The novel is regarded as a medium that not only presents the beauty of language but also reflects the dynamics of social life, such as human relationships, the value and meaning of friendship, economic struggles, and the search for meaning in life. Using a descriptive qualitative approach with literary aesthetic analysis, this study examines intrinsic elements and language styles that construct aesthetic value while conveying moral and social messages. The results indicate that literary aesthetics in this novel function as a means of representing social reality in a symbolic and reflective manner, thereby raising readers’ awareness of the social conditions around them. Thus, literary works serve not only as entertainment but also as a reflection and critique of social reality.